Unraveling the Role of Cognition in the Internationalization Process - Bressan, Flávio; Morini, Cristiano; Inácio Júnior, Edmundo; Garcia Fuentes, Elisabet (Internext, 2020)
Objective: The aim of this paper is to verify the effects of triggering stimuli on internationalization and whether, according to the target population, ambidexterity and mental models (MM) increase the predisposition to exports, as well as whether the country of origin causes differences in terms of cognition. Method: Data collection consisted of applying a questionnaire to a sample of 285 students from Business Administration programs in Brazil and Spain. ANOVA Welsh was used to verify the heterogeneity of variations, the Kolmogorov-Smirnov and Shapiro-Wilk tests were used to assess normality, and nonparametric Kruskal-Wallis tests were used to verify the results of the previous tests. Main outcomes: The results showed that the strategic MM facilitates internationalization. In the sample studied, it was possible to verify that Brazilians show an operational tendency, with decisions based on logic and an improvised lifestyle, which denotes lower possibility of engaging in internationalization. This differs from what was found in the Spanish sample, which showed tendency to a strategic approach, denoting greater possibility of engagement in an internationalization process. These results may also be used to improve internationalization stimulus programs, considering cognitive aspects. Relevance: There is a low number of references relating the subject of ambidexterity to the internationalization process. This study is relevant for proposing the creation of indexes to obtain data on the MM and ambidexterity regarding the identification of personal motivation factors influencing the entrepreneur’s insertion in international markets. Theoretical/methodological contributions: Proposition of a formula for standardizing and rescaling the instruments’ value, as the differences between scales may contribute to the inclusion of a hidden dimension of the internationalization process: the analysis of cognition.